2020
DOI: 10.17485/ijst/v13i23.636
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-based energy efficient smart street lighting system

Abstract: Background/Objectives: Pakistan is experiencing significant energy crises for the last two decades. The increasing power demand cannot be controlled with traditional energy techniques. The conventional street lighting system remains ON all over the night. Consequently, a huge amount of energy is wasted. To overcome the shortage of energy, an efficient smart lighting system is proposed. Methods: The prime thought to accomplish is``Energy on-demand'' i.e. handed-in wherever, whenever required. To achieve this go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In SL control, YOLO is considered as the optimal choice due to its speed, efficiency, and ability to detect multiple objects simultaneously. When combined with other sensors, YOLO can reduce processing time and enable quick adjustments in lighting intensity based on detected pedestrians or vehicles [141]. Additionally, YOLO exhibits strong generalization performance, making it effective in handling diverse traffic scenarios and lighting conditions.…”
Section: User-driven Controlmentioning
confidence: 99%
“…In SL control, YOLO is considered as the optimal choice due to its speed, efficiency, and ability to detect multiple objects simultaneously. When combined with other sensors, YOLO can reduce processing time and enable quick adjustments in lighting intensity based on detected pedestrians or vehicles [141]. Additionally, YOLO exhibits strong generalization performance, making it effective in handling diverse traffic scenarios and lighting conditions.…”
Section: User-driven Controlmentioning
confidence: 99%
“…The unique property of street light is that it is ubiquitous. Omar et al [61] revealed that because street lamps are a necessary facility of a city, the consumption of streetlamps will also affect the economic condition of a country. Adjusting the street light is tricky because if it is too dim, it will affect the safety of road users.…”
Section: Implementation Target 1) Street Smart Lightingmentioning
confidence: 99%